Peran Marketing dalam Dunia Politik - Letty Aziz, Nyimas Latifah (Pusat Penelitian Politik, 2008)
The Implementation of multiparty system in Indonesia nowadays has made political parties compete in achieving their goals In order to achieve those goals political parties need strategy in catching public attention This strategy is an implementation ofmarketing science in political arena or better known as political marketing To be specific the strategy is called by marketing practitioners as product promotion price dan place (4P).